IMPLEMENTATION OF THE PRINCIPLE OF JUSTICE IN THE PROFIT-SHARING SYSTEM IN FINANCING MUDHARABAH at PT. BANK MUAMALAT INDONESIA Tbk. KCU MATARAM - Fitriani; Suharti (International Journal of Islamic and Social Sciences (ISOS), 2021)
This study aimed to determine the implementation of the principle of justice in the profit-sharing system on mudharabah financing at PT Bank Muamalat Indonesia Tbk. KCU Mataram. The research method was descriptive qualitative research. The data collection techniques were carried out using observation, interviews and documentation. Meanwhile, data analysis was carried out inductively using some steps consisting of data reduction, data presentation, and conclusions. The results showed that the profit-sharing system in mudharabah financing at PT Bank Muamalat Indonesia Tbk. KCU Mataram implemented a revenue sharing system using the profit projection method based on the customer's business results data and the customer's ability to pay in monthly installments. The principle of fairness in the profit-sharing system in mudharabah financing laid on the willingness of the parties ( sohibul maal and mudharib ) to bear the profits and losses proportionally according to the portion of their respective involvement.